A-Stable High Order Hybrid Linear Multistep Methods for Stiff Problems. Issue 4 (December 2014) - Okuonghae, R. I.
This paper considers a new class of high order hybrid linear multistep methods for the numerical solution of stiff initial value problems (IVPs) in ordinary differential equations (ODEs). The numerical experiments shows the application of the methods on stiff problems.